2006
DOI: 10.1007/s11064-006-9233-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Plasma Biopterin Levels in Psychiatric Disorders Suggests a Common BH4 Deficit in Schizophrenia and Schizoaffective Disorder

Abstract: Tetrahydrobiopterin (BH4) is an essential cofactor for amine neurotransmitter synthesis. BH4 also stimulates and modulates the glutamatergic system, and regulates the synthesis of nitric oxide by nitric oxide synthases. A connection between BH4 deficiencies and psychiatric disorders has been previously reported; major depression and obsessive-compulsive disorder have been found in subjects with a BH4 deficiency disorder and more recently we have observed a robust plasma deficit of biopterin (a measure of BH4),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 54 publications
3
18
0
2
Order By: Relevance
“…This assumption may be justified when the molecular mechanisms of psychosis are of prime interest. Molecular abnormalities common for schizophrenia and schizoaffective disorder have been documented (Richardson et al, 2007). Genetic linkage studies suggest that functional psychosis is a spectrum of clinical phenotypes controlled by overlapping sets of susceptibility genes (Craddock et al, 2006; Craddock et al, 2005; Craddock and Owen, 2005; Hamshere et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This assumption may be justified when the molecular mechanisms of psychosis are of prime interest. Molecular abnormalities common for schizophrenia and schizoaffective disorder have been documented (Richardson et al, 2007). Genetic linkage studies suggest that functional psychosis is a spectrum of clinical phenotypes controlled by overlapping sets of susceptibility genes (Craddock et al, 2006; Craddock et al, 2005; Craddock and Owen, 2005; Hamshere et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that total biopterin levels were only low in plasma and but not in urine of patients diagnosed with schizophrenia (59). In contrast, more recent studies found profound reductions in plasma total biopterin levels in schizophrenia and schizoaffective patients (by 34% and 25%, respectively) compared to normal controls (60,61). Meta-analysis studies for the International Database of BH4 Deficiencies found significant correlation between biopterin levels in plasma and CSF but failed to establish such a correlation between biopterin levels in urine and CSF of schizophrenia patients (60).…”
Section: Tetrahydrobiopterin In Schizophreniamentioning
confidence: 98%
“…BH4 is ubiquitous and is likely present in all cells and tissues but current knowledge of the regulatory mechanism of BH4 in the brain is far from complete [14]. BH4 also modulates glutamatergic system function and regulates nitric oxide production [15]. BH4 deficit has previously been reported in schizophrenia patients relative to healthy controls [16].…”
Section: Introductionmentioning
confidence: 99%